The Influence of Decisional and Emotional Forgiveness on Attributions - Lichtenfeld, Stephanie; Maier, Markus A.; Buechner, Vanessa L.; Fernández Capo, Maria (Frontiers in Psychology, 2019)
Research on forgiveness suggests that forgiveness is an emotion-focused coping process important for clinical settings as it can promote both physical and mental health [1, 2]. Investigating antecedents of forgiveness, empirical studies and theoretical models propose that attributions influence forgiveness. However, hardly any studies or theoretical models have ever looked at the possibility that this relationship may be reciprocal in nature and investigated if forgiveness also impacts a victim’s attributions. The present, highly powered (n=969) study seeks to fill this gap and provides the first empirical support that emotional forgiveness has a strong influence on subsequent attributions. Specifically, individuals, who have emotionally forgiven a transgression, hold the transgressor less responsible for the offense compared to those in the decisional forgiveness and the control condition. Moreover, the findings conceptually replicate previous research [3] by demonstrating that emotional but not decisional forgiveness affect cognition and thus, emotional and decisional forgiveness should be treated as distinct facets in the forgiveness process. Implications of these results for clinical and health psychology are discussed.